Age-related changes in static balance in older women aged in their early sixties to their late eighties: different aging patterns in the anterior–posterior and mediolateral directions - Sasagawa, Shun; Arakawa, Ai; Furuyama, Aimi; Matsumoto, Yasuo (Frontiers in Aging Neuroscience, 2024)
The aim of this study was to cross-sectionally investigate how static balance changes throughout the ageing process in older women aged from their early sixties to their late eighties.Methods: Forty-six older women (aged 62-89 years) were requested to stand barefoot and quietly on a force platform for 30 seconds with their eyes either open or closed. During the trials, the position of the center of foot pressure (CoP) and the acceleration of the body's center of mass (ACC) were measured. The root mean square (RMS) of the CoP and ACC values was calculated to evaluate the amplitude of postural sway and the level of regulatory activity, respectively. The mean power frequency of the ACC was also calculated to represent the temporal characteristics of regulatory activity.Results: In the anterior-posterior direction, there was no significant relationship between the RMS of CoP and the participants' age, whereas the RMS of ACC significantly increased with increasing age. In the mediolateral direction, however, the RMS of CoP significantly increased with increasing age, whereas the RMS of ACC did not change with age. The mean power frequency of ACC did not exhibit any age-related change in either the anterior-posterior or the mediolateral direction.The results indicate that static balance in older women aged in their early sixties to their late eighties exhibits distinctly contrasting aging patterns between the anterior-posterior and mediolateral directions. To prevent falls in older women, it is necessary to elucidate the physiological mechanisms responsible for the increase in mediolateral sway that occurs throughout old age.